Targeting the Retinoid X Receptor Pathway Prevents and Ameliorates Murine Chronic Graft-Versus-Host Disease - Thangavelu, Govindarajan; Zaiken, Michael C.; Mohamed, Fathima A.; Flynn, Ryan; Du, Jing; Rhee, Stephanie Y.; Riddle, Megan J.; Aguilar, Ethan G.; Panoskaltsis-Mortari, Angela; Sanders, Martin E.; Blazar, Bruce R. (Frontiers in Immunology, 2022)
Most allogeneic hematopoietic stem cell transplant (allo-HSCT) recipients receive peripheral blood stem cell grafts resulting in a 30-70% incidence of chronic graft-vs-host disease (cGVHD), a major cause of mortality and morbidity in long-term survivors. While systemic steroids remain the standard of care for first line therapy, patients may require long-term administration and those with steroid resistant or refractory cGVHD have a worse prognosis. Although durable and deep responses with second line therapies can be achieved in some patients, there remains an urgent need for new therapies. In this study, we evaluated the efficacy of IRX4204, a novel agonist that activates RXRs and is in clinical trials, to prevent and treat cGVHD in two complementary murine models. In a major histocompatibility complex mismatched, non-sclerodermatous multiorgan system model with bronchiolitis obliterans, IRX4204 prevented and reversed cGVHD including associated pulmonary dysfunction with restoration of germinal center T follicular helper: T follicular regulatory cell balance. In a minor histocompatibility antigen disparate sclerodermatous model, IRX4204 treatment significantly prevented and ameliorated skin cGVHD by reducing Th1 and Th17 differentiation due its anti-inflammatory properties. Together, these results indicate that IRX4204 is a promising therapeutic option to treat cGVHD with bronchiolitis obliterans or sclerodermatous manifestations.